2008
DOI: 10.3348/kjr.2008.9.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Publication Rates for Abstracts Presented by Korean Investigators at Major Radiology Meetings

Abstract: Objective: To determine the publication rate of abstracts presented by Korean investigators at national and international radiological meetings, and to identify predictive factors of publication. Materials and Methods:Abstracts presented at the annual meetings of the Korean Radiological Society (KRS), and abstracts presented by Korean investigators at the annual meetings of the Radiological Society of North America (RSNA) and European Congress of Radiology (ECR) from 2001 to 2002 were searched for subsequent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 28 publications
3
58
0
Order By: Relevance
“…In a survey of the literature, the publication rate of papers from a variety of specialties ranged between 8.5% and 78% (6). Worldwide, only a few investigations exist concerning radiology meetings, which report rates ranging 11%-47% (1)(2)(3)(4)(5)(6)(7)(8). According to a study evaluating Turkish radiology meetings in years 1995-2002, the overall publication rate was 11% (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of the literature, the publication rate of papers from a variety of specialties ranged between 8.5% and 78% (6). Worldwide, only a few investigations exist concerning radiology meetings, which report rates ranging 11%-47% (1)(2)(3)(4)(5)(6)(7)(8). According to a study evaluating Turkish radiology meetings in years 1995-2002, the overall publication rate was 11% (1).…”
mentioning
confidence: 99%
“…Abstract presentations at national meetings allow a rapid transfer of knowledge in summarizing current research and focusing future research endeavors (1)(2)(3)(4)(5). In spite of the fact that many studies are of sufficient value for presentation in these sessions, only the most instructive and highest quality studies are worthy of full-text publication in a peer-reviewed journal (2).…”
mentioning
confidence: 99%
“…Moreover, experimental research is often performed by academic trainees working in active research teams. Therefore, it may encourage them to subsequently publish their results [11]. However, others have reported opposite results [2,7,10].…”
Section: Discussionmentioning
confidence: 97%
“…Some of these could be interpreted as a sign of more intense scientific commitment. Indeed, a prospective design generally indicates a clear effort towards more thorough studies, and has been already reported [10,11,15,16]. Moreover, experimental research is often performed by academic trainees working in active research teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation